Women's property rights in Bangladesh: what is practically happening in South Asian rural communities - Karim, A.H.M Zehadul (Medwell Publishing, 2012)
From religious and normative point of view, Women in rural Bangladesh may legally claim their inheritance of the paternal property through a hereditary rule of succession, which is also prescribed by the traditionally been prevailing in the rural areas of the country. Among the rural communities in Bangladesh, land and any other properties, can be inherited legally and conventionally, by both boys and girls; but usually, this line of inheritance does only prevail among those who live there permanently with their parents, even after marriage. Ideally, a woman within the family appears to have nearly an equal right to property, having legally claimed a half of the share of a man, which is a common practice representing the religious customs. But women's customary rights of property ownership, often cease to continue, as soon as they leave their parents' house to move out with their husbands after marriage at distant places. In legal context though, the scriptural and normative rules partially recognize their claim to paternal property, but in actuality, the women eventually dispossess them, because of the prevalence of a stereotyped community ideology. In Bangladesh, there is a predominant social stigma, where a woman always will have low symbolic family status, if she claims her paternal property. A devout woman in this regard, often is well-respected by her family and community. The scriptural legislation therefore, becomes very much ineffective, by way of showing a clear deprivation of the women property rights. Based on empirical data collected through an anthropological method, from two remote villages in the northern part of the country, the paper explains analytically as to what cultural understandings support this inherent contemptible South Asian pattern of the women property rights in rural Bangladesh.